Impact of Exogenous Gonadotropin Stimulation on Circulatory and Follicular Fluid Cytokine Profiles - Baskind, N. Ellissa; Orsi, Nicolas M.; Sharma, Vinay (International Journal of Reproductive Medicine, 2014)
Background. The natural cycle is the prototype to which we aspire to emulate in assisted reproduction techniques. Increasing evidence is emerging that controlled ovarian hyperstimulation (COH) with exogenous gonadotropins may be detrimental to oogenesis, embryo quality, and endometrial receptivity. This research aimed at assessing the impact of COH on the intrafollicular milieu by comparing follicular fluid (FF) cytokine profiles during stimulated in vitro fertilization (IVF) and modified natural cycle (MNC) IVF. Methods. Ten women undergoing COH IVF and 10 matched women undergoing MNC IVF were recruited for this pilot study. 40 FF cytokine concentrations from individual follicles and plasma were measured by fluid-phase multiplex immunoassay. Demographic/cycle/cytokine data were compared and correlations between cytokines were computed. Results. No significant differences were found between COH and MNC groups for patient and cycle demographics, including outcome. Overall mean FF cytokine levels were higher in the MNC group for 29/40 cytokines, significantly so for leukaemia inhibitory factor and stromal cell-derived factor-1α. Furthermore, FF MNC cytokine correlations were significantly stronger than for COH data. Conclusions. These findings suggest that COH perturbs intrafollicular cytokine networks, in terms of both cytokine levels and their interrelationships. This may impact oocyte maturation/fertilization and embryo developmental competence.